ATP-independent CFTR channel gating and allosteric modulation by phosphorylation - Wang, Wei (National Academy of Sciences, 2010)
Cystic fibrosis (CF) is caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) channel, an ATP binding cassette (ABC) transporter. CFTR gating is linked to ATP binding and dimerization of its two nucleotide binding domains (NBDs). Channel activation also requires phosphorylation of the R domain by poorly understood mechanisms. Unlike conventional ligand-gated channels, CFTR is an ATPase for which ligand (ATP) release typically involves nucleotide hydrolysis. The extent to which CFTR gating conforms to classic allosteric schemes of ligand activation is unclear. Here, we describe point mutations in the CFTR cytosolic loops that markedly increase ATP-independent (constitutive) channel activity. This finding is consistent with an allosteric gating mechanism in which ligand shifts the equilibrium between inactive and active states but is not essential for channel opening. Constitutive mutations mapped to the putative symmetry axis of CFTR based on the crystal structures of related ABC transporters, a common theme for activating mutations in ligand-gated channels. Furthermore, the ATP sensitivity of channel activation was strongly enhanced by these constitutive mutations, as predicted for an allosteric mechanism (reciprocity between protein activation and ligand occupancy). Introducing constitutive mutations into CFTR channels that cannot open in response to ATP (i.e., the G551D CF mutant and an NBD2-deletion mutant) substantially rescued their activities. Importantly, constitutive mutants that opened without ATP or NBD2 still required R domain phosphorylation for optimal activity. Our results confirm that (i) CFTR gating exhibits features of protein allostery that are shared with conventional ligand-gated channels and (ii) the R domain modulates CFTR activity independent of ATP-induced NBD dimerization.